Use of power factor and specific point energy as design parameters in laser powder-bed-fusion (L-PBF) of AlSi10Mg alloy. (15th November 2019) - Zavala-Arredondo, Miguel; London, Tyler; Allen, Madie; Maccio, Tomaso; Ward, Sam; Griffiths, David; Allison, Amanda; Goodwin, Paul; Hauser, Carl
Abstract: The densification mechanism in L-PBF of AlSi10Mg alloy with varying process parameters has been investigated. The suitability of using volumetric [Jmm −3 ], areal [Jmm −2 ] and linear [Jmm −1 ] energy density as design parameters is discussed. To compare process conditions between continuous and pulsed laser systems, the jump speed vj of a pulsed L-PBF system is calculated by means of an experimentally validated FE thermal model previously developed at TWI. The importance of using vj in scan speed calculations is demonstrated. This allowed calculation of accurate energy levels comparable to optimal conditions reported in literature. The power factor (PF ) model and the specific point energy (ESP ), used to describe and replicate the laser welding process in different laser systems, have been adapted to describe the L-PBF process. ESP - PF curve is introduced, showing optimal processing windows applicable to different L-PBF systems with powers ranging from 175 to 967 W and laser focus diameter from 75 to 300 μm. Quantitative indicators for hatch spacing and layer thickness optimisation are presented for processing AlSi10Mg alloy: 1) melt-width overlapping coefficient ≥ 30%, 2) width-to-depth ratio ≥ 0.8 (using the measured half width) and 3) melt-depth limit <410 μm. Graphical abstract: Unlabelled Image Highlights: Characterisation of porosity formation with varying process parameters in laser powder-bed-fusion of AlSi10Mg alloy. Quantitative melt-pool indicators for optimal additive manufacturing of as-built AlSi10Mg components. L-PBF experiments and simulations for optimised calculation of point-to-point speed in a pulsed-mode laser system. Novel approach for characterising optimal process conditions using the power factor model and specific point energy.